2019
DOI: 10.1590/s0100-83582019370100045
|View full text |Cite
|
Sign up to set email alerts
|

Differential Hormetic Response of Fenoxaprop-p-Ethyl Resistant and Susceptible Phalaris minor Populations: a Potential Factor in Resistance Evolution

Abstract: Resistance evolution in weeds against all major herbicide groups demand investigations to identify various factors responsible for resistance development. Herbicide hormesis has not yet been included in the list of factors promoting the evolution of resistance. Studies were conducted to evaluate the degree of hormesis in fenoxaprop-p-ethyl susceptible and resistant Phalaris minor to provide a first indication of whether hormesis is a potential factor in the development of resistance. In the first experiment, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Hormesis could theoretically cause better growth and increased competitiveness in both biotypes of E. colona without considering mechanical and precision application technologies for glyphosate spraying. There is a probability that growth stimulation via hormesis, makes weeds more competitive, more reproductive and more resistant to other control treatments and it can alter dynamics of weed-crop competition [10,14,42,43]. If stimulated weeds are resistant to herbicides in the field, hormesis can directly facilitate the evolution of resistance by improving their growth and reproductive output [6,17,42,44].…”
Section: Plos Onementioning
confidence: 99%
“…Hormesis could theoretically cause better growth and increased competitiveness in both biotypes of E. colona without considering mechanical and precision application technologies for glyphosate spraying. There is a probability that growth stimulation via hormesis, makes weeds more competitive, more reproductive and more resistant to other control treatments and it can alter dynamics of weed-crop competition [10,14,42,43]. If stimulated weeds are resistant to herbicides in the field, hormesis can directly facilitate the evolution of resistance by improving their growth and reproductive output [6,17,42,44].…”
Section: Plos Onementioning
confidence: 99%
“…Under such scenarios, changes in weed species composition, and hence herbicide susceptibility, are expected (Belz and Duke 2017;Cedergreen 2008aCedergreen , 2008b. Growth stimulation caused by ultralow herbicide doses has recently been demonstrated as an important factor conducive to herbicide-resistance development, and hormetically boosted resistant biotypes are expected to be more competitive (Farooq et al 2019). Differential hormetic responses were exhibited by fenoxaprop p-ethyl resistant and susceptible populations of canary grass (Phalaris minor Retz.).…”
Section: Buds and Seed Productionmentioning
confidence: 99%
“…Differential hormetic responses were exhibited by fenoxaprop p-ethyl resistant and susceptible populations of canary grass (Phalaris minor Retz.). The upper limit of stimulatory hormetic dose (16% to 24% of the recommended application rate) for the resistant population was inhibitory for the susceptible population (Farooq et al 2019). Likewise, another study found a 54% increase in biomass of an acetyl-CoA carboxylase target-site resistant (TSR) biotype of blackgrass (Alopecurus myosuroides Huds.)…”
Section: Buds and Seed Productionmentioning
confidence: 99%
“…It was shown that the irradiation of seeds before sowing provides an increase in productivity of about 5-20% (Farooq et al, 2019). Such an increase in yield after irradiation or after the action of other physical factors is explained by the presence of a metabolic acceleration zone on the dose curve and the yield as well.…”
Section: Introductionmentioning
confidence: 99%